Differential and strain-specific triggering of bovine alveolar macrophage effector functions by mycoplasmas - Jungi, T.W.; Krampe, M.; Sileghem, M.R.; Griot, C.; Nicolet, J. (Elsevier, 1996)
Mycoplasma strains being considered as pathogenic or non-pathogenic for cattle were tested on their capacity to activate bovine alveolar macrophages in vitro. Of particular interest was the behaviour of Mycoplasma mycoides ssp. mycoides small colony type (M.m.m. SC), the causative agent of contagious bovine pleuropneumonia (CBPP). Increases in procoagulant activity (PCA), tumor necrosis factor-?- (TNF-?) and nitrogen monoxide (NO) generation were tested. To minimize an influence of macrophage activation by mycoplasmagrowth media, mycoplasmas were cultured on embryonic calf nose epithelial cells. The three macrophage functions tested were not correlated, but were differentially induced in strain-specific manner. Four out of seven strains induced PCA, regardless of pathogenicity, and all strains promoted moderate NO generation at high concentrations. All tested M.m.m, SC strains (Afadé, L2 and PG1), and the pathogenic M. bovis, induced TNF-? product ion at low concentrations (106 colony forming units per ml). M. sp. serogroup 7 and the non-pathogenic M. bovirhinis and Acholeplasma laidlawii did not induce TNF-? up to 108 cfu/ml. Thus, strain-specific differences are reflected in differential macrophage activation patterns. The findings are consistent with an important role for TNF-? in pathogenesis of CBPP.